Effects of 2.5 s mouse nerve growth factor on regeneration of injured sciatic nerves in mice and rats - Wang Jun-Zhi; Bai De-Cheng; Rao Chun-Ming; Li Wen-Guang; Gao Ming-Tang; Wang Xiao-Qi; Wu Yong-Jie (Acta Pharmacologica Sinica, 2016)
AIM: To study the promoting activity of 2.5 s murine nerve growth factor (NGF) for the regeneration of injuried sciatic nerve. METHODS: The sciatic nerves of mice and rats were crushed. The axon counts and differential axon counts were made. Evoked potential latency (NMEPL) was recorded at sites of proximal (Pro) and distal (Dis) segment of soleus muscles. RESULTS: In mice, NGF im 0.5-1 kBU.kg-1 increased the axon counts of regenerated nerves 20 d after crush; 2-4 kBU.kg-1 simultaneously alleviated the denervated atrophy of soleus muscles. In rats, NGF i.m. increased the axon counts at dose of 1 kBU.kg-1 for 40 d, 2 kBU.kg-1 for 30 d and 40 d, and 4 kBU.kg-1 for 20 d, 30 d and 40 d after crush; the number of large axons of regenerated nerves were also increased by NGF i.m. 2 kBU.kg-1 for 40 d and 4 kBU.kg-1 for 30 d and 40 d; Pro NMEPL was shortened by NGF 1, 2, and 4 kBU.kg-1, Dis-NMEPL was shortened by NGF 2 and 4 kBU.kg-1 for 40 d. CONCLUSION: NGF im evidently promotes the regeneration of injuried sciatic nerve, and attenuates the skeletal muscular atrophy caused by nerve injury.